Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Honda dan Loyalitas Konsumen di PT. Supra Jaya Abadi - Edbert Christian; Apriansyah Ramadani; Vany Tanisha Salim; Acai Sudirman (IPM2KPE, 2023)
This research aims to test and analyze the influence of product quality, price and promotion on Honda motorbike purchasing decisions and consumer loyalty. The research method used is quantitative research with the sample used being 146 consumers. Regarding the quality of existing products, PT Supra Jaya Abadi still has problems regarding complaints about motorbike spare parts offered by the company. The prices offered are competitive with other similar dealers and also offer various promotions for consumers for cash or credit purchases and also discounts for Honda motorbike services. Dominant promotions are only given to buyers who buy motorbikes on credit, such as price cuts, reduced credit down payments, reduced installment payments, while cash purchases get promotions from free service, fewer jackets and helmets. Conclusion, product quality has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, promotion has a positive and significant effect on purchasing decisions, customer satisfaction positively and significantly mediates the effect of product quality on customer loyalty, satisfaction results are positive and significant customers mediate the effect of price on customer loyalty. Keywords: Price, Product Quality, Purchasing Decisions, Promotion